Effects of artificial sweeteners on the quality parameters of yogurt during storage - Sakandar, Hafiz Arbab; Huma, Nuzhat; Sadiq, Faizan Ahmed; Khan, Qaiser Farid; Rehman, Abdur; Imran, Muhammad; Perveen, Rashida; Sameen, Ayesha (Progress in Nutrition, 2018)
Yoghurt is one of the famous nutritious fermented milk products which have myriad of positive health effects on human beings and curable against different intestinal diseases. This research was conducted to observe the effects of different artificial sweeteners on the quality parameters of yoghurt with relation to storage. Some people are allergic to natural sweeteners so artificial sweetener will be helpful for them. Physico-chemical, microbiology and various sensory evaluation tests were carried out with the interval of 7, 14, 21 and 28 days. It was determined from this study that addition of artificial sweeteners in yoghurt has shown much harmful effects on the yoghurt microorganisms and other physicochemical parameters from quality point of view. Significantly good results for acceptance were obtained when aspartame was added in yoghurt at level of 0.022 percent. In addition, growth of beneficial microorganisms in yoghurt was also improved as well as other sensory attributes were enhanced by the addition of aspartame.